Phylogenetic comparison of Desulfotomaculum species of subgroup 1a and description of Desulfotomaculum reducens sp. nov. - Visser, Michael (2016)
A genome and physiological comparison was made of the type strains of Desulfotomaculum species belonging to subgroup 1a and of Desulfotomaculum reducens strain MI-1. Phenotypically, Desulfotomaculum reducens strain MI-1 can be distinguished from the other described Desulfotomaculum species of subgroup 1a by its ability to grow with propionate and butyrate. In addition, the strain is able to use a variety of metals as electron acceptors. Metal reduction has not been tested in the other species, but seems likely based on our genome analysis. Phylogenetic 16S rRNA gene sequence analysis and the average nucleotide identity between the genomes of the species of subgroup 1a show that strain MI-1 represents a novel species within the Desulfotomaculum 1a subgroup, Desulfotomaculum reducens sp. nov. The type strain is MI-1T.